2008
DOI: 10.4103/0301-4738.40356
|View full text |Cite
|
Sign up to set email alerts
|

An observational study of the proceedings of the All India Ophthalmological Conference, 2000 and subsequent publication in indexed journals

Abstract: Aims:To determine the quality of reporting in the proceedings of the All India Ophthalmological Conference (AIOC) 2000, subsequent rate of publication in an indexed journal and differences between the proceedings and the journal version of these papers.Design:Observational study.Materials and Methods:All papers presented at the AIOC 2000 were retrieved from the proceedings and assessed for completeness of reporting. To determine the subsequent full publication, a Medline search was performed as of January 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 22 publications
0
25
1
2
Order By: Relevance
“…This proportion of publication is much less than that reported from other studies studying this aspect of presentations at international conferences in different areas of medicine [2][3][4][5][6][7]. There were no previous English language studies related to neonatology to compare the present study findings, though a publication rate of 45 % was reported from a perinatology conference [9].…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…This proportion of publication is much less than that reported from other studies studying this aspect of presentations at international conferences in different areas of medicine [2][3][4][5][6][7]. There were no previous English language studies related to neonatology to compare the present study findings, though a publication rate of 45 % was reported from a perinatology conference [9].…”
Section: Discussioncontrasting
confidence: 81%
“…A systematic review of reports examining the rate of full publication of results presented as abstracts showed that more than a third of abstracts presented at biomedical meetings would ultimately remain unpublished in full [2]. Individual researchers have reported the subsequent publication rate of conference abstracts to vary from 16.5 to 78 % at varying periods (up to six years) after the meeting [3][4][5][6][7], depending on specialty and other factors. As there have been no previous studies on papers presented at Neonatology conferences, the present study was conducted to document the publication rate of papers presented at the Annual Convention of National Neonatology Forum of India, and study the factors associated with their subsequent publication.…”
Section: Introductionmentioning
confidence: 99%
“…A dissertation reveals results and informs readers about the related subject. However, if it is not published in a scientific journal, it will gain access to only a limited audience and thus will be unable to achieve its objective (4). A dissertation should be published as a scientific article to contribute to the national or international scientific literature.…”
Section: Discussionmentioning
confidence: 99%
“…Tıp Eğitimi the world. 14 In ad di ti on, it en han ces the aca de mic and pro fes si o nal cre di bi lity of the re se arc hers, as well as that of the de part ment and of the ins ti tu tion. The streng the ning of sci en ti fic edu ca ti on is a key com po nent in de ve lo ping com pe tent physi cians who will not only ask the right qu es ti ons but al so be ab le to apply cur rent tre at ment met ho dolo gi es.…”
Section: Figurementioning
confidence: 99%